1987
DOI: 10.1111/j.1600-0404.1987.tb03542.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of theophylline and phenobarbital on rat brain 5′-nucleotidase

Abstract: Xanthines and barbiturates have opposing effects on cerebral function and metabolism. Since the xanthine theophylline is known to inhibit the enzyme 5'-nucleotidase, and thus endogenic adenosine release, an in vitro experiment was conducted on the assumption that theophylline and phenobarbital may have an opposing effect on 5'-nucleotidase activity. This assumption was confirmed. The hypothesis that barbiturates in general cause an increase in endogenic adenosine release seems compatible with the known functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Studies showed a significant inhibition of rabbit renal 5Ј-nucleotidase (EC 3.1.3.5), cyclic nucleotide phosphodiesterase (EC 3.1.4.17), and adenosine deaminase (EC 3.5.4.4) by theophylline, but only at millimolar concentration (17). Furthermore, a significant inhibition of a 5Ј-nucleotidase from rat brain by different xanthine derivatives has been observed (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed a significant inhibition of rabbit renal 5Ј-nucleotidase (EC 3.1.3.5), cyclic nucleotide phosphodiesterase (EC 3.1.4.17), and adenosine deaminase (EC 3.5.4.4) by theophylline, but only at millimolar concentration (17). Furthermore, a significant inhibition of a 5Ј-nucleotidase from rat brain by different xanthine derivatives has been observed (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Theophylline is known to be a nonspecific antagonist of P1 receptors, 1,2) and inhibitor of cyclic nucleotide phosphodiesterase, 2,10) 5-nucleotidase, 11,12) and alkaline phosphatase, 13) and a weak inhibitor of HGPT. 14,15) As previously reported, 4) theophylline had no effect on the Ado-induced ATP levels in PC12 cells without pretreatment.…”
Section: Discussionmentioning
confidence: 99%